Recreational Mathematics – A Hands-on Activity to Encourage Interest in Learning Mathematics - Hassan, Khairil Bariyyah; Md. Khalid, Rahayu; Kamaruddin, Hasnur Hidayah; Mohammad Nawawi, Norazah; Seuk Fei, Yeow; Shaari, Mohd Fairuz; Azman, Hazeeq Hazwan (Multidisciplinary Applied Research and Innovation, 2021)
Students learn Matheatics in a variety of ways, and it is recommended that teachers and parents use a hands-on activity to encourage students’ interest towards Science, Technology, Engineering and Mathematics (STEM) subjects. The Recreational Mathematics kit is designed to promote primary school students’ interest towards the subject. This kit has been used in two programs, Mathematics and Science Day at SK La Salle, Sentul, and STEM Day at UNISEL in year 2019. Total of 100 participants between the age of seven to twelve years old were involved for both programs. Universiti Selangor’s Mathematics lecturers and students participated as facilitators and mentors. This kit contained three hands-on activities: Number Hunt, Polygon Puzzle and Shadow Adventure. All the activities involved basic arithmetic concept and help to develop students’ problem-solving skills, creativity skills and critical thinking skills.  Each activity was guided by facilitators and mentors. Throughout this activity, finding shows that 85% of the students agreed that they felt happy and enjoyed learning mathematics through games and activities, and it increases their interest to learn the subject. More than 80% of the students agreed on the systematic program management and are interested with the method guided. However, this kit only covers 3 activities related to basic Algebraic operations, polygon and ratio. More games covering other topics in Mathematics will be added into this kit in future to increase students’ interest and awareness on the important of STEM subjects, especially Mathematics.